The Lausiac history - Palladius, Bishop of Aspuna, -approximately 430.; Wortley, John; Bartelink, G. J. M. (Gerhardus Johannes Marinus) (Athens, Ohio : Cistercian Publications ; Collegeville, Minnesota : Liturgical Press, 2015)
Born in Galatia in the 360s, Palladius enrolled as a monk on the Mount of Olives in his early twenties. As a monk, he traveled to Alexandria, the desert of Nitria, the Cells, Palestine, Rome, and the Thebaid. During his travels he encountered Rufinus of Aquileia, Melania the Elder, the hermit Dorotheos, Macarius of Alexandria, Evagrius of Pontus, Jerome of Bethlehem, and John Chrysostom. He wrote this elegant account of his visits to various monastic sites in Egypt toward the end of the fourth century AD for the imperial chamberlain Lausus. It is both the most sophisticated and the most informative of the few documents illustrating the earliest chapter in the history of Christian monasticism. Palladius's work is the only one of the major monastic writings not written for fellow monks to inspire them with models for their emulation but rather for a man very much of the world, with the explicit intention of exerting not only religious but also political influence.
An English translation of the Lausiac history, based on the critical edition of the Greek text published by G.J.M. Bartelink in 1974 under the title La storia Lausiaca.
Includes bibliographical references (pages 145-147).
Print version record.
Keywords: Palladius, -- Bishop of Aspuna, -- -approximately 430.; Lausiac history (Palladius, Bishop of Aspuna); Christian biography -- Egypt -- Early works to 1800.; Monasticism and religious orders -- Egypt -- History -- Early church, ca. 30-600 -- Sources; Desert Fathers; Christian biography; Desert Fathers; Monasticism and religious orders -- Early church; Egypt; RELIGION / Institutions & Organizations; Electronic books; Electronic books; Early works; History; Sources